Fatigue may improve equally after balance and endurance training in multiple sclerosis: a randomised, crossover clinical trial - Perucca, Laura; Scarano, Stefano; Russo, Giovanna; Robecchi Majnardi, Antonio; Caronni, Antonio (Frontiers in Neurology, 2024)
Introduction Fatigue and poor balance are frequent and severe problems in multiple sclerosis (MS) that may interact. Endurance training is known to be effective on fatigue. This study aims to test if balance training is more effective against MS fatigue. Methods A randomised crossover trial was run, recruiting 31 MS people (21 women; median age: 46 years, range: 30–64; median EDSS: 4, range: 2.5–5). Participants received balance and endurance training alternately (15 one-to-one sessions, 5 days/week) and were assessed before (T0), after (T1), and 30 days after treatment ended (T2). The Modified Fatigue Impact Scale (MFIS) with scores linearised through Rasch analysis was the primary outcome (the lower the measure, the better the condition, i.e., the lower the fatigue symptoms). The Equiscale balance scale and posturography (EquiTest) were used to assess balance. Linear mixed-effects models with ANOVA were used for significance testing. Results Thirteen participants had no carryover effect and were included in the primary analysis. Fatigue significantly changed across the three time points (F2,58 = 16.0; p < 0.001), but no difference across treatments was found. Altogether, both treatments significantly improved the MFIS measure at T1 (95%CI: −1.24 logits; mean: −1.67 to −0.81 logits) and T2 (95%CI: −1.04; mean: −1.49 to −0.60) compared to T0 (95%CI: −0.51; mean: −0.95 to −0.08; p ≤ 0.001). Equiscale and posturography highlighted balance improvement after balance training but not after endurance training. Conclusion Balance and endurance training could similarly reduce fatigue in MS patients in the short term. However, only balance training also improved balance in MS.